Personal finance after 50 for dummies - Tyson, Eric (Eric Kevin) (--For dummies., 2018)
Personal Finance After 50 For Dummies, 2nd Edition (9781119543633) was previously published as Personal Finance After 50 For Dummies, 2nd Edition (9781119118770). While this version features a new Dummies cover and design, the content is the same as the prior release and should not be considered a new or updated product. Manage your finances in your golden years-enjoy your retirement! Numerous life changes come with the territory of getting older-as we're reminded every day by anti-aging campaigns-but one change the media doesn't often mention is the need for a shifting approach to personal financial management. Personal Finance After 50 For Dummies, 2nd Edition offers the targeted information you need to make informed decisions regarding your investments, spending, and how to best protect your wealth. You've worked your whole life for your nest egg-why not manage it as effectively as possible? Enjoying your golden years hinges on your ability to live the life you've dreamed of, and that's not possible unless you manage your finances accordingly. The right financial decisions may mean the difference between a condo in a more tropical climate and five more years of shoveling snow, so why leave them to chance? Explore financial advice that's targeted to the needs of your generation Understand how changes in government programs can impact your retirement Consider the implications of tax law updates, and how to best protect your assets when filling out tax forms each year Navigate your saving and investment options, and pick the approaches that best fit the economic environment Whether you're heading into your senior years or your parents are getting older and you want to help them take care of their finances, Personal Finance After 50 For Dummies, 2nd Edition offers the insight you need to keep financial matters on the right track!